XX a. masinės statybos gyvenamųjų kompleksų fenomenas Lietuvoje Europiniame industrinės statybos kontekste - Dijokienė, Dalia; Džervus, Petras (Journal of Architecture and Urbanism, 2011)
The 20th century phenomenon of large-scale construction of residential areas in Lithuania within the context of European industrialized construction At the beginning of the 20th century, urban development in Europe and worldwide was marked by a breakthrough of a new phenomenon in the field of planning and construction – the industrialized housing construction. Residential districts that were constructed in order to meet a massive housing demand determined by intensive urbanization processes have left a significant mark in many European cities. The article analyses residential districts of large-scale construction and circumstances that determined formation of this phenomenon (from ideas to consequences of their implementation). Attention is drawn to crucial political decisions taken by the countries concerned relating to industrialization and promotion of large-scale constructions. A comparative analysis is carried out with a view to determining the scale and characteristics of this phenomenon in various countries. In case of Lithuania, residential complexes and districts of large-scale construction built in six major cities of the country are reviewed, including analysis of their position in the current urban structure, comparison of the size of their territories with that of the towns’ administrative and urbanized areas. Article in Lithuanian. Santrauka. XX a. pradžia pasaulio ir Europos urbanistikos raidoje pasižymi naujo pobūdžio projektavimo ir statybos proveržiu – industrinės gyvenamosios statybos fenomenu. Gyvenamieji rajonai, statyti spartiems miestų urbanizacijos procesams reikalaujant didelio kiekio gyvenamųjų būstų, daugelyje Europos miestų paliko žymų pėdsaką. Straipsnyje nagrinėjami masinės statybos gyvenamieji rajonai bei jų atsiradimo aplinkybės (nuo idėjų iki realizacijos pasekmių). Paliečiami fenomenui esminės įtakos turėję nagrinėjamų valstybių politiniai sprendimai, susiję su masinės statybos industrializavimu ir propagavimu. Atliekama lyginamoji analizė, norint išsiaiškinti esminį fenomeno mastą ir ypatumus skirtingose valstybėse. Lietuvos atveju apžvelgiami šešiuose didžiuosiuose miestuose suprojektuoti ir įgyvendinti masinės statybos gyvenamieji kompleksai bei rajonai, nustatoma jų padėtis dabartinėje miestų struktūroje, užimama teritorija palyginama su miesto administraciniu plotu bei urbanizuotu miesto plotu. Reikšminiai žodžiai: industrinė statyba, masinė gyvenamoji statyba, gyvenamasis kompleksas, gyvenamasis rajonas, mikrorajonas, urbanistinė struktūra. First Publish Online: 22 May 2013